Penderaan fizikal di kalangan kanak-kanak pada 1993: satu kajian kes kawalan di Hospital Kuala Lumpur - Khoo, K.B.; Ch'ng, G.S.; Muhd Khairi O.; Jesni J.; Kamid M.; Zaidah M.A.; Raja Liza R.A. (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 1995)
A case control study was conducted on 83 reported cases of physical abuse among children aged 0 -18 years old who were admitted ti Hospital Kuala Lumpur in 1993. The purpose of the study was to study the distribution of physical abuse among children and to determine the relationship between various risk factors such as socioeconomic status and family structure with parents, younger fathers or working mothers. Others factors such as maternal age, parents' total income and educational level, position of the abused child in the family and the number of siblings were not shown to have a statistically significant association with physical abuse.